1980
DOI: 10.1128/iai.28.1.65-73.1980
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of cell wall peptidoglycan by strains of Streptococcus mutans and Streptococcus sanguis

Abstract: Turnover of the cell wall peptidoglycan fraction of six different strains of Streptococcus mutans and eight different strains of Streptococcus sanguis was examined. Cells were grown in the presence of [3H]lysine and ['4C]leucine for at least eight generations and then chased in growth medium lacking the two labels. At intervals during the chase, samples of cultures were removed, and the amounts of the two labeled precursors remaining in the peptidoglycan and protein fractions were quantitated. Similar experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
1
4
1
Order By: Relevance
“…Thus, release of the protease to the environment may reflect a natural turnover and shedding of the surface components. However, two other viridans group streptococci, S. mutans and S. sanguis, have been found to not release peptidoglycan fragments into the culture medium during growth (30). This apparent discrepancy from our findings may be explained by the use of TCA precipitation methods by these investigators in their determination of enzymatic degradation of radiolabeled peptidoglycan.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, release of the protease to the environment may reflect a natural turnover and shedding of the surface components. However, two other viridans group streptococci, S. mutans and S. sanguis, have been found to not release peptidoglycan fragments into the culture medium during growth (30). This apparent discrepancy from our findings may be explained by the use of TCA precipitation methods by these investigators in their determination of enzymatic degradation of radiolabeled peptidoglycan.…”
Section: Discussioncontrasting
confidence: 99%
“…2). Residual protein indicated by 14C in during growth counts reached a final value of approximately in total trichloro-4% of starting 14C counts after 1 h. In two in T-layer protein additional experiments, counts were 14 and 11% derived from 0. pared with values reported for some other grampositive bacteria (3,16); however, Hungerer and Tipper (14) reported that the peptidoglycan of B. sphaericus 9602, which also contains a T-layer, constituted only 23% of the mass of the cell wall.…”
Section: So -supporting
confidence: 60%
“…The modified Park and Hancock procedure 60 was investigated to determine the amount of c residual contaminating protein and possible hy-40 ;t drolysis of peptidoglycan by hot trichloroacetic acid (3) or pronase (16). Log phase cells labeled with [14C]valine or [3H]lysine were heated in 5% 20 trichloroacetic acid at 100°C for 6 min and subjected to the procedure for measurement of peptidoglycan, using various incubation times in 1 mg of pronase per ml.…”
Section: So -mentioning
confidence: 99%
“…For determining the loss of insoluble peptidoglycan, analyses were carried out in different buffers by methods recently described (8,16). Treatments with HEWL (100 ,ug/ml), protease (0.1 to 10 ,ug/ml), and HEWL plus protease were examined for their effects upon the cell wall peptidoglycan of S. mutans GS5 (5.6 x 108 cells per ml) before and after treatment with sodium thiocyanate (final concentration, 0.1 m).…”
mentioning
confidence: 99%